„A usta znów rozluźniają się do słów okaleczałych” – namopaniki Aleksandra Wata (recepcja, język, interpretacja) - Graf, Magdalena; Graf, Paweł (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The authors of the article, knowing about Wat’s interest in language mechanisms, focus their attention on namopaniki – the genre created by the poet. Arguing with the previous findings which concentrated on the presentation of the properties of semantics of the non-rational futuristic word, they propose an interpretation based on the demonstration of the inner energy of text.